Neurocognitive function in relation to blood lead among young men prior to chronic occupational exposure - Cai-Guo Yu; Wen-Yi Yang; Nelly Saenen; Fang-Fei Wei; Zhen-Yu Zhang; Blerim Mujaj; Lutgarde Thijs; Ying-Mei Feng; Tim S Nawrot; Jan A Staessen (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: Higher than contemporary exposure levels and advanced age of study participants have limited the interpretation of previous studies relating neurocognitive function to lead exposure. We reassessed this association in young American men prior to chronic occupational exposure at lead recycling plants, using baseline measurements of the Study for Promotion of Health in Recycling Lead (NCT02243904). METHODS: We administered the Stroop test (ST) and the digit-symbol test (DST) to 339 men (mean age, 28.6 years; participation rate 82.7%). Whole blood lead (BL) was determined by inductively coupled plasma mass spectrometry and related ST and DST test results using multivariable-adjusted regression. RESULTS: Average values were 4.26 μg/dL for BL, 1624 ms and 1474 ms for mean reaction time in incongruent and congruent ST trials, and 109 sec for mean total latency in DST. The number of participants with fully correct answers amounted to 281 (82.9%) and 334 (98.5%) in incongruent and congruent ST trials, respectively, and to 198 (58.4%) in the DST. In multivariable-adjusted analyses, there was no association between cognitive performance and BL except for a weak but opposite association in DST; for a 10-fold BL increment, mean total latency was 5.4% (95% confidence interval, -0.4‒11.5%; P=0.066) higher, whereas the error score was 42% (-10‒69%; P=0.096) lower. To exclude an effect of the cumulative lead dose, sensitivity analyses restricted to workers <40, 35 and 30 years were confirmatory. CONCLUSIONS: At the exposure levels in our current study, we failed to demonstrate a consistent inverse association of BL with neurocognitive performance in young American men.